Microsporidia Can Acquire Lamin‐like Intermediate Filaments and Cell Adhesion Catenin‐cadherin Complexes from the Host (?). (2nd July 2020) - Weidner, Earl; Sokolova, Yuliya Y.; Overstreet, Robin M.
Abstract: On their spore surfaces, Microsporidia often develop a canopy of filaments with characteristics of intermediate filaments (IF), as we demonstrated in previous studies on Thelohania sp., Ameson michaelis, and S praguea lophii . Genomic studies indicate that among invertebrates, lamins that may localize in the cytoplasm or nucleus, are the only known IF type. These IFs can bind to the substrate containing cell adhesion molecules (CAMs) cadherins, associated with β and γ catenins. The objects of this study were to determine whether microsporidia have CAMs with the attached IFs on their envelopes and to find out if these proteins are provided by the host. An examination was made for localization of lamins and CAMs on the spores of the mentioned above species and Anncaliia algerae, plus in the host animals. Then, we determined whether the spores of A. michaelis and A. algerae could bind vertebrate nuclear lamin onto the spore surface. We also tested transgenic Drosophila melanogaster stocks bearing cadherin‐GFP to see whether developing A. algerae parasites in these hosts could acquire host CAMs. The tests were positive for all these experiments. We hypothesize that microsporidia are able to acquire host lamin IFs and cell adhesion catenin–cadherin complexes from the host.